Food security and panchayati raj - Chaturvedi, Pradeep 1946-; Indian Association for the Advancement of Science; Food and Agriculture Organization of the United Nations; National Conference on "Panchayati Raj - the key to Food Security and Nutrition" (1996 : New Delhi, India) (New Delhi : Concept, 1997)
Papers presented at the National Conference on "Panchayat Raj - the key to Food Security and Nutrition' at the New Delhi, India, on 2-3 July, 1996
Includes bibliographical references and index
Keywords: Panchayat -- India -- Congresses; Local governemnt -- India -- Congresses; Food supply -- India -- Rural conditions -- Congresses; Nutrition policy -- India -- Rural conditions -- Congresses